Building Customer Loyalty: The Impact of Price Perception and Service Quality Mediated by Customer Satisfaction - Muhammad, Baginda; Simon, Zainal Zawir; Suryono, Dwi Windu (SAN Scientific, 2024)
This research aims to analyze the influence of price and service quality on customer loyalty through customer satisfaction as an intervening variable. The type of research used in this research is explanatory research. The population in this research is customers. Data analysis uses the Partial Least Square Structural Equation Modeling Method. The results of this research show that (1) price perception has a positive and significant effect on customer loyalty, (2) service quality has a positive and significant effect on customer loyalty, (3) price perception has no effect on customer satisfaction, (4) service quality has a positive effect and significant effect on customer satisfaction, (5) customer satisfaction has a positive and significant effect on customer loyalty, (6) customer satisfaction cannot mediate the effect of price perception on customer loyalty, (7) customer satisfaction can mediate the effect of service quality on customer loyalty. Managerial Implications The study's findings indicate that perceptions of price and service quality significantly influence customer loyalty, with customer satisfaction serving as a crucial intervening variable. Managers should focus on optimizing both price perception and service quality to enhance overall customer satisfaction, which in turn increases customer loyalty.